Da paixão à perversão: um estudo psicanalitico acerca das repercussões do abuso sexual incestuoso na constituição psíquica feminina - Brida, Glaucia Valéria Pinheiro de (2013)
The present psychoanalytical research aims to investigate the repercussions of incestuous sexual abuse engendered by the father on daughter s psychic constitution. This is a clinical research based on supervision of psychological treatment to people in situation of sexual violence. The theoretical reference that based this thesis is psychoanalysis, which settles that the incestuous sexual abuse of girls is linked to children sexual fantasies and with femininity structuring. Having observed passionate relationships in clinic cases of women who were victims of incest when children, the present work defends the thesis that incestuous sexual abuse engendered by the father promotes the establishment of the daughter s perversion. Such thesis is founded on Sigmund Freud s work on his theory concerning feminine psychic and perversion, and also on Piera Aulagnier s theory concerning historic reality and the desire and parents speech on dialectic of identification and self constitution, and on perversion and passionate relationships as manifestations of polymorphic potential. Two supervision clinic cases were examined and we conclude that incestuous sexual abuse engendered by the father during childhood perverts femininity through the girl s narcissistic disqualification as object of desire